Different expression of circulating microRNA profile in tibetan OSAHS with metabolic syndrome patients - Xue-feng Shi; Xiang He; Ze-rui Sun; Jie Duo; Hao Yang (Scientific Reports)
Abstract Recent empirical investigations reinforce the understanding of a profound interconnection between metabolic functions and Obstructive Sleep Apnea-hypopnea Syndrome (OSAHS). This study identifies distinctive miRNA signatures in OSAHS with Metabolic Syndrome (Mets) patients from healthy subjects, that could serve as diagnostic biomarkers or describe differential molecular mechanisms with potential therapeutic implications. In this study, OSAHS with MetS patients showed significantly higher Apnea Hyponea Index(AHI), but lower oxygen desaturation index(ODI 4/h) and minimum pulse oxygen saturation(SpO2). A total of 33 differentially expressed miRNAs by Limma method, and 31 differentially expressed miRNAs by DEseq2 method were screened. In addition, GO enrichment analysis of target genes associated with differentially expressed miRNAs revealed significant enrichment in metabolic processes, suggesting that the differential expression of OSAHS-induced miRNAs may contribute to the progression of metabolic disorders through the regulation of metabolic pathways. Furthermore, KEGG pathway enrichment analysis revealed significant enrichment in the p53 signaling pathway and several other pathways. Notably, the Wnt signaling pathway, PI3K-Akt signaling pathway, cAMP signaling pathway, and AMPK signaling pathway are implicated in the metabolic processes of glucose dysregulation and lipid homeostasis, as well as the pathogenesis of hypertension associated with OSAHS. We identified IKBKB, PIK3R1, and MAP2K1 as the target genes most associated with Mets pathogenesis in OSAHS, regulated by miR-503-5p, miR-497-5p, and miR-497-5p, respectively. Additionally, the target genes of differentially expressed miRNAs between Tibetan OSAHS patients with MetS and healthy individuals are regulated by transcription factors such as NR2C1, STAT3, STAT5a, HIF1a, ETV4, NANOG, RELA, SP1, E2F1, NFKB1, AR, and MYC. In conlusion, we found differentially expressed miRNAs in Tibetan OSAHS patients with Metabolic Syndrome for the first time. Enrichment analysis results suggest that differentially expressed miRNAs may involved in the development of OSAHS-related metabolic disorders by regulating metabolic pathways. We also revealed that IKBKB, PIK3R1, and MAP2K1 are mostly associated with metabolic disorder in OSAHS, and miR-503-5p and miR-497-5p may regulate the development of MetS associated with OSAHS by modulating IKBKB, PIK3R1, and MAP2K1.